The role of auxin in nitrogen-modulated shoot branching. - Hou, M.; Wu, D.; Li, Y.; Tao, W.; Chao, L.; Zhang, Y
Shoot branching is determined by axillary bud formation and outgrowth and remains one of the most variable determinants of yield in many crops. Plant nitrogen (N)acquired mainly in the forms of nitrate and ammonium from soil, dominates plant development, and high-yield crop production relies heavily on N fertilization. In this review, the regulation of axillary bud outgrowth by N availability and forms is summarized in plant species. The mechanisms of auxin function in this process have been well characterized and reviewed, while recent literature has highlighted that auxin export from a bud plays a critical role in N-modulating this process
Keywords: AUXIN